Metalloprotease-disintegrin ADAM12 actively promotes the stem cell-like phenotype in claudin-low breast cancer - Duhachek-Muggy, Sara; Qi, Yue; Wise, Randi; Alyahya, Linda; Li, Hui; Hodge, Jacob; Zolkiewska, Anna (My University, 2017)
Background: ADAM12 is upregulated in human breast cancers and is a predictor of chemoresistance in estrogen receptor-negative tumors. ADAM12 is induced during epithelial-to-mesenchymal transition, a feature associated with claudin-low breast tumors, which are enriched in cancer stem cell (CSC) markers. It is currently unknown whether ADAM12 plays an active role in promoting the CSC phenotype in breast cancer cells. Methods: ADAM12 expression was downregulated in representative claudin-low breast cancer cell lines, SUM159PT and Hs578T, using siRNA transfection or inducible shRNA expression. Cell characteristics commonly associated with the CSC phenotype in vitro (cell migration, invasion, anoikis resistance, mammosphere formation, ALDH activity, and expression of the CD44 and CD24 cell surface markers) and in vivo (tumor formation in mice using limiting dilution transplantation assays) were evaluated. RNA sequencing was performed to identify global gene expression changes after ADAM12 knockdown. Results: We found that sorted SUM159PT cell populations with high ADAM12 levels had elevated expression of CSC markers and an increased ability to form mammospheres. ADAM12 knockdown reduced cell migration and invasion, decreased anoikis resistance, and compromised mammosphere formation. ADAM12 knockdown also diminished ALDEFLUOR(+) and CD44(hi)/CD24(-/lo) CSC-enriched populations in vitro and reduced tumorigenesis in mice in vivo. RNA sequencing identified a significant overlap between ADAM12-and Epidermal Growth Factor Receptor (EGFR)-regulated genes. Consequently, ADAM12 knockdown lowered the basal activation level of EGFR, and this effect was abolished by batimastat, a metalloproteinase inhibitor. Furthermore, incubation of cells with exogenously added EGF prevented the downregulation of CD44(hi)/CD24(-/lo) cell population by ADAM12 knockdown. Conclusions: These results indicate that ADAM12 actively supports the CSC phenotype in claudin-low breast cancer cells via modulation of the EGFR pathway.
Citation: Duhachek-Muggy, S., Qi, Y., Wise, R., Alyahya, L., Li, H., Hodge, J., & Zolkiewska, A. (2017). Metalloprotease-disintegrin ADAM12 actively promotes the stem cell-like phenotype in claudin-low breast cancer. Molecular Cancer, 16, 18. doi:10.1186/s12943-017-0599-6
Keywords: Breast Cancer; Cancer Stem Cells; Epidermal Growth Factor Receptor; Epithelial-To-Mesenchymal Transition; Adam Metalloprotease; Growth-Factor Receptor